Niche-Specific Adaptive Evolution of Lactobacillus plantarum Strains Isolated From Human Feces and Paocai - Pan, Qiqi; Cen, Shi; Yu, Leilei; Tian, Fengwei; Zhao, Jianxin; Zhang, Hao; Chen, Wei; Zhai, Qixiao (Frontiers in Cellular and Infection Microbiology, 2021)
Lactobacillus plantarum, a widely used probiotic in the food industry, exists in diverse habitats, which has led to its niche-specific genetic evolution. However, the relationship between this type of genetic evolution and the bacterial phenotype remains unclear. Here, six L. plantarum strains derived from paocai and human feces were analyzed at the genomic and phenotypic levels to investigate the features of adaptive evolution in different habitats. A comparative genomic analysis showed that 93 metabolism-related genes underwent structural variations (SVs) during adaptive evolution, including genes responsible for carbohydrate, lipid, amino acid, inorganic ion and coenzyme transport and metabolism, and energy production and conversion. Notably, seven virulence factor-related genes in strains from both habitats showed SVs — similar to the pattern found in the orthologous virulence genes of pathogenic bacteria shared similar niches, suggesting the possibility of horizontal gene transfer. These genomic variations further influenced the metabolic abilities of strains and their interactions with the commensal microbiota in the host intestine. Compared with the strains from feces, those from paocai exhibited a shorter stagnation period and a higher growth rate in a diluted paocai solution because of variations in functional genes. In addition, opposite correlations were identified between the relative abundances of L. plantarum strains and the genus Bifidobacterium in two media inoculated with strains from the two habitats. Overall, our findings revealed that the niche-specific genetic evolution of L. plantarum strains is associated with their fermentation abilities and physiological functions in host gut health. This knowledge can help guiding the exploration and application of probiotics from the specific niches-based probiotic exploitation.